High humidity environment increases FBG by impairing the intestinal barrier - Wang, Yao; Zhuang, Kai; Yi, Qiuxia; Wu, Yalan; Luo, Yi; Ouyang, Yulin; Li, Liang; Li, Chun; Luo, Huanhuan (Frontiers in Immunology, 2025)
IntroductionClimate and environmental changes pose significant threats to human metabolic health; however, the specific effects of individual environmental factors on metabolic diseases remain poorly understood. This study aimed to investigate the impact of a high humidity environment (HH) on fasting blood glucose (FBG), intestinal barrier integrity, and gut microbiota composition.MethodsWe analyzed clinical samples collected during HH exposure and performed a controlled male mouse experiment. FBG and hormone levels were assessed, and intestinal barrier integrity was evaluated using western blot and immunofluorescence staining. Gut microbiota composition was profiled via 16S rDNA sequencing. Mechanistic insights were obtained through fecal microbiota transplantation (FMT), Mendelian randomization (MR) analysis, and metabolomic profiling. An antibiotic cocktail (ABX) intervention was applied to determine the reversibility of HH-induced effects.ResultsClinical samples collected under HH conditions showed elevated FBG, increased glucagon (GC) levels, impaired intestinal barrier function, and decreased serum gamma-aminobutyric acid (GABA) concentrations. 16S rDNA sequencing revealed increased abundances of Alistipes, Parabacteroides, and Akkermansia. Metabolomic analysis demonstrated reduced serum GABA levels, which correlated with intestinal barrier disruption and activation of the MDP-NOD2 pathway in pancreatic β-cells. HH exposure also downregulated GAD67 expression, reducing GABA synthesis and leading to enhanced GC secretion from islet α-cells. FMT suggested that gut microbiota alterations mediated HH-induced FBG elevation. ABX treatment effectively reversed these metabolic and microbial changes.DiscussionOur findings demonstrate that a high humidity environment disrupts gut microbiota homeostasis, impairs the intestinal barrier, and reduces GABA synthesis in pancreatic β-cells, thereby promoting the development of type 2 diabetes mellitus (T2DM).